2000
DOI: 10.1007/s004310051314
|View full text |Cite
|
Sign up to set email alerts
|

Hydrops fetalis associated with erythrocyte pyruvate kinase deficiency

Abstract: The authors report a case of hydrops fetalis due to severe pyruvate kinase de®ciency, the most unusual clinical manifestation of this disease. Conclusion Pyruvate kinase de®ciency, as other erythrocyte enzymopathies, must be considered in the dierential diagnosis of non-immune hydrops fetalis. This has important implications for clinical investigations, therapy and genetic counselling. Key words Pyruvate kinase á Haemolytic anaemia á Hydrops fetalis á MutationsAbbreviations G6PD glucose-6-phosphate dehydrogena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 2 publications
1
29
0
Order By: Relevance
“…Some PK-deficient patients present with hydrops fetalis. 89 Reticulocytosis is almost always observed. Splenectomy often ameliorates the hemolysis, especially in severe cases, and increases reticulocyte counts even further.…”
Section: Pyruvate Kinasementioning
confidence: 99%
“…Some PK-deficient patients present with hydrops fetalis. 89 Reticulocytosis is almost always observed. Splenectomy often ameliorates the hemolysis, especially in severe cases, and increases reticulocyte counts even further.…”
Section: Pyruvate Kinasementioning
confidence: 99%
“…11 Nonimmune hydrops fetalis may be associated with all other congenital hemolytic anemias. [14][15] The diagnosis of HLH was made according to the guidelines of the Histiocyte Society Criteria 8 with pancytopenia, splenomegaly, hypofibrinogenemia, prominent hemophagocytosis and increased We did not detect an underlying disease causing secondary HLH. Parental consanguinity was also suggestive for primary HLH.…”
Section: Discussionmentioning
confidence: 99%
“…2 Prenatal deaths have been reported in subjects severely deficient in glucosephosphate isomerase, 21,22 PK, [23][24][25] and hexokinase. 26 With the use of molecular biology techniques, prenatal genetic testing for RBC enzyme deficiencies has become possible, facilitating the management of severe prenatal hemolytic anemia.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Although subjects with PK deficiency show a moderate degree of hemolytic anemia, the most severe cases die in utero 4,5 or are transfusion-dependent. 6 Repeated red blood cell (RBC) transfusions may induce hemochromatosis, 7 and a recent report showed that free hemoglobin caused by intravascular hemolysis might interfere with the biological action of nitric oxide, leading to the development of pulmonary hypertension.…”
mentioning
confidence: 99%